Mucoadhesive polyethylenimine–dextran sulfate nanoparticles containing Punica granatum peel extract as a novel sustained-release antimicrobial. (June 2015) - Tiyaboonchai, Waree; Rodleang, Ingdao; Ounaroon, Anan
Abstract Mucoadhesive polyethylenimine–dextran sulfate nanoparticles (PDNPs) were developed for local oral mucosa delivery. Punica granatum peel extract (PGE) was loaded into PDNPs for oral malodor reduction and caries prevention. PDNPs were constructed using the polyelectrolyte complexation technique employing oppositely charged polymers polyethylenimine (PEI) and dextran sulfate (DS), with PEG 400 as a stabilizer. Under optimal conditions, spherical particles of ∼500 nm with a zeta potential of ∼+28 mV were produced. Up to 98%, drug entrapment efficiency was observed. The mass ratio of PEI:DS played a significant role in controlling particle size and entrapment efficacy. PDNPs shown to be a good mucoadhesive drug delivery system as confirmed by ex vivo wash off test. In vitro dissolution studies revealed that PGE-loaded PDNPs manifested a prolong release characteristic with a burst release within 5 min. In addition, they remained effectively against oral bacteria.